2019
DOI: 10.3389/fped.2019.00050
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, Molecular, and Clinical Characterization of Patients With Primary Carnitine Deficiency via Large-Scale Newborn Screening in Xuzhou Area

Abstract: Background: Primary carnitine deficiency (PCD) is attributed to a variation in the SLC22A5 (OCTN2) gene which encodes the key protein of the carnitine cycle, the OCTN2 carnitine transporter. PCD is typically identified in childhood by either hypoketotic hypoglycemia, or skeletal and cardiac myopathy. The aim of this study was to the clinical, biochemical, and molecular characteristics of PCD patients via newborn screening with tandem mass spectrometry (MS/MS). Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 27 publications
1
19
2
Order By: Relevance
“…However, if maternal carnitine deficiency was included in the analysis, it could be concluded that carnitine deficiency was more common in the region. c.1400C>G in the SLC22A5 gene for PCD and c.1031A>G in the ACADS gene for SCADD were common mutations, consistent with previous reports 10 12 , 34 . However, of the 3 cases diagnosed with MCADD, 2 cases with dizygotic twins carried a homozygous c.985A>G (66.7%) mutation in the ACADM gene, so we think that the mutation frequency of c.985A>G seems to be overestimated in this study.…”
Section: Discussionsupporting
confidence: 92%
“…However, if maternal carnitine deficiency was included in the analysis, it could be concluded that carnitine deficiency was more common in the region. c.1400C>G in the SLC22A5 gene for PCD and c.1031A>G in the ACADS gene for SCADD were common mutations, consistent with previous reports 10 12 , 34 . However, of the 3 cases diagnosed with MCADD, 2 cases with dizygotic twins carried a homozygous c.985A>G (66.7%) mutation in the ACADM gene, so we think that the mutation frequency of c.985A>G seems to be overestimated in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Based on NBS including second-tier genetic screening, the incidence of PCD in the selected population was estimated at 1:8191. This incidence is higher than that reported in most other regions of China [9,22,23]. Although there may be regional differences, our findings suggest that the true incidence of PCD in China might be underestimated.…”
Section: Discussioncontrasting
confidence: 72%
“…The incidence of PCD in selected population was estimated at 1:8191 by incorporating second-tier genetic screening into NBS programs. The incidence is higher than that reported in most region of China [9,27,28]. Of course there may be regional differences, but our ndings suggest that the true incidence of PCD in China might be much underestimated.…”
Section: Discussioncontrasting
confidence: 58%